2014
DOI: 10.4103/0975-962x.140820
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gonial angle determination from cephalograms and orthopantomogram

Abstract: Introduction:Gonial angle is an important parameter of the craniofacial complex giving an indication about the vertical parameters and symmetry of the facial skeleton. Both orthopantomogram (OPG) and lateral cephalograms can be used for the measurement of gonial angle. Because of the superimpositions seen on lateral cephalograms, reliable measurement of the gonial angle becomes difficult. The aim of the present study is to check the possible application and reliability of OPG for gonial angle determination by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 8 publications
3
28
2
1
Order By: Relevance
“…The mean values of the right and the left gonial angles measured using the panoramic radiographs also did not show a statistically significant difference. The results of this study were in accordance with the findings of Larheim et al5 and Bhullar et al,12 who reported no statistically significant differences in the gonial angle measured using lateral cephalograms and panoramic radiographs. Mattila et al7 measured the gonial angle using panoramic radiographs and lateral cephalograms, compared the values with those found using dry skulls, and concluded that the measurements made using the panoramic radiographs were more accurate, which is contrary to the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The mean values of the right and the left gonial angles measured using the panoramic radiographs also did not show a statistically significant difference. The results of this study were in accordance with the findings of Larheim et al5 and Bhullar et al,12 who reported no statistically significant differences in the gonial angle measured using lateral cephalograms and panoramic radiographs. Mattila et al7 measured the gonial angle using panoramic radiographs and lateral cephalograms, compared the values with those found using dry skulls, and concluded that the measurements made using the panoramic radiographs were more accurate, which is contrary to the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…13,[14][15][16] Several researcher's have compared the two types of radiographs for predicting cephalometric gonial angle. [17][18][19][20][21][22] Ul Haq MH / Memon S / Agha D Bibi T in their study reported significant correlation between the cephalometric and panoramic values and concludes that panoramic radiography is as reliable as lateral cephalogram in predicting vertical facial pattern as assessed by gonial angle. 18 In an other study statistically insignificant difference was found in the gonial angle measured by two different radiographic methods in three different types of occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, as compared with LCR, PR is not yet reliable enough to provide sufficiently accurate additional information (4). In addition, no reports have specified a detailed method for drawing the inferior border of the mandible (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Thus, the important points for tracing on film were reviewed in this report.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to evaluate the similarity of the GA on PR and LCR. PR has several advantages over LCR, including the ability to evaluate mandibular asymmetry (4,12) and mandibular growth direction (2-4,35,36), the separate and clear measurement of both the right and left GA (12,20), relatively low radiation exposure (37)(38)(39), and the possibility of greater clinical versatility. It has been reported that the GA is wider for edentulous persons than for dentate individuals (6-11), perhaps because of morphological changes secondary to tooth loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation